Characterization of periattachment factor - Purcell, Scott H., author; Anthony, Russell V., advisor; Seidel, George E., advisor (Colorado State University. Libraries, 2008)
The purpose of these studies was to characterize expression of periattachment factor (PF) mRNA in the developing sheep conceptus, localize PF in the sheep conceptus, determine if degrading PF mRNA in the sheep conceptus was detrimental to development, and characterize PF in human tissues and cells. Sheep conceptuses were collected on d 11, 13, 15, 16, 17, 21, and 30 post-mating. oPF mRNA exhibited a quadratic expression pattern (P<0.05). No oPF mRNA was detected in d 11 conceptuses. From d 13, oPF mRNA increased to a peak at d 16 before declining. Peak expression of oPF mRNA in the conceptus occurs during rapid elongation and initial attachment of the conceptus to the endometrium. Immunolocalization of PF in a d 15 conceptus showed predominantly nuclear staining in trophectoderm and trophendoderm. Next, embryos collected from superovulated ewes on d 8 post-mating were infected with either a lentivirus expressing a short-hairpin (sh) RNA designed to target PF mRNA for degradation, a lentivirus expressing a shRNA containing 3 mismatched nucleotides, or a control lentivirus expressing no shRNA. Following infection, blastocysts were transferred into recipient ewes and collected back on d 15 of gestation. While 94 and 88% of the control and mismatched shRNA-treated conceptuses elongated by d 15, none of the embryos treated with the lentivirus expressing shRNA against PF mRNA elongated, and most died. This indicates that oPF is required for conceptus elongation and survival. Human PF mRNA was detected in human carcinomas and in the first trimester cytotrophoblast cell line, hTR8. Immunohistochemistry showed PF in the nuclei of carcinomas and in first and second trimester cytotrophoblasts. PF was also present in the invading cytotrophoblast columns. In an in vitro invasion assay of first trimester cytotrophoblasts, hPF mRNA increased from 0, 3, to 12 h as invasion occurred. To further characterize PF in human cells, a lentiviral construct expressing an shRNA targeting the hPF mRNA sequence was developed that resulted in 63% mRNA reduction in BeWo cells.
Keywords: implantation; periattachment factor; trophoblasts; physiology